Personalized approach in the treatment of thyroid cancer: A review - Zamira Ah.-G. Radzhabova (ZAO "Consilium Medicum", 2022)
The main goal is to improve treatment outcomes of disseminated inoperable thyroid cancer through a personalized choice of targeted agents. Considering gene mutations in drug choice will further improve the survival of patients with rare mutations. Despite the small sample of patients, mutation detection, regardless of localization, and basket studies will allow future results to be obtained much faster than in a dozen years and use these results in this rare category of patients. Basket studies allow patients with rare disorders to receive personalized therapy according to mutations in tumor tissue, regardless of the affected organ.